Introducing the Inhabiting Technique; highlighting the value of psychophysical processes originated by Konstantin Stanislavski, while showing that most aspects of Stanislavski's System of Active Analysis are inappropriate for use with Shakespeare; inviting the actor into the role of Psychopomp. Issue 1 (2nd January 2019) - Harrison, Susan-Jane
ABSTRACT: A sharing of practice-based research occurring in actor training labs, this paper will explore subjective findings regarding a new technique called Inhabiting, with reference to inspiration gained at The S-Word Symposium. Investigation of the author's early psychophysical experiences as theatre practitioner form the foundation of this research. The goal of this work has been to define a new psychophysical method grounded in, but not limited to Active Analysis. Inhabiting is developing in response to American acting students, who feel limited and inhibited by The Method. Inhabiting advocates a form of active analysis (improvisatory, up-on-your-feet-exploration) in combination with somatic techniques. This paper makes the case that Inhabiting is especially appropriate for use with Shakespeare, but that Stanislavski's Active Analysis, when directly applied to classical text can limit the actor's expressive capacity. This writing outlines how Inhabiting assists actors to work flexibly with emotion by framing the body as an instrument. Inhabiting has developed out of investigative psychophysical theatre practice. Drawing on the work of Laban, Linklater, Patsy Rodenberg, Cicely Berry, Stanislavski, Grotowski, and Richard Schechner, Inhabiting is taught in actor labs and stresses exploration over getting it right, framing discovery as a starting place for potential mastery. Through learning how to engage a body primed and wired with emotional triggers, the actor begins to trust that everything she needs she already has. Through psychophysical practices like Inhabiting, actors have the potential to embody the sacred role of Psychopomp for their audiences.